Differentiation of Lactobacillus plantarum, L. pentosus, and L. paraplantarum by recA Gene Sequence Analysis and Multiplex PCR Assay with recA Gene-Derived Primers - Torriani, Sandra (American Society for Microbiology, 2001)
In this study, we succeeded in differentiating Lactobacillus plantarum, Lactobacillus pentosus, and Lactobacillus paraplantarum by means of recA gene sequence comparison. Short homologous regions of about 360 bp were amplified by PCR with degenerate consensus primers, sequenced, and analyzed, and 322 bp were considered for the inference of phylogenetic trees. Phylograms, obtained by parsimony, maximum likelihood, and analysis of data matrices with the neighbor-joining model, were coherent and clearly separated the three species. The validity of the recA gene and RecA protein as phylogenetic markers is discussed. Based on the same sequences, species-specific primers were designed, and a multiplex PCR protocol for the simultaneous distinction of these bacteria was optimized. The sizes of the amplicons were 318 bp for L. plantarum, 218 bp for L. pentosus, and 107 bp for L. paraplantarum. This strategy permitted the unambiguous identification of strains belonging to L. plantarum, L. pentosus, and L. paraplantarum in a single reaction, indicating its applicability to the speciation of isolates of the L. plantarum group.